2017
DOI: 10.33087/ekonomis.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION (Studi Pada Karyawan Perusahaan Jasa Multi Finance Di Kota Jambi)

Abstract: This research aims to know the factors that affect employee turnover intention on multi services companies in finance in the city of jambi. The study is quantitative research is an investigation about the social issues based on testing a theory consisting of variables, measured by numbers, and analyzed with statistical procedures to determine whether the correct theory of the predictive generalizations. The respondents in this study i.e., employees at the companies services multi finance in the city of Jambi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
2
0
9
Order By: Relevance
“…Sedangkan menurut (Etnaningtiyas 2011) yaitu personalityjob fit, pendidikan, usia, dan jenis kelamin. Sedangkan menurut (Firdaus 2017) turnover intention dipengaruhi oleh kepuasan kerja dan komitmen organisasi. Sedangkan menurut(Ramasari and Wahyuningtyas 2014) ada 4 faktor yang mempengaruhi turnover intention di suatu perusahaan, yaitu stres kerja, kepuasan kerja, pengembangan karir, dan komitmen organisasi.…”
Section: Masukunclassified
“…Sedangkan menurut (Etnaningtiyas 2011) yaitu personalityjob fit, pendidikan, usia, dan jenis kelamin. Sedangkan menurut (Firdaus 2017) turnover intention dipengaruhi oleh kepuasan kerja dan komitmen organisasi. Sedangkan menurut(Ramasari and Wahyuningtyas 2014) ada 4 faktor yang mempengaruhi turnover intention di suatu perusahaan, yaitu stres kerja, kepuasan kerja, pengembangan karir, dan komitmen organisasi.…”
Section: Masukunclassified
“…Oleh sebab itu proses seleksi melibatkan uji kompetensi, tes psikologi dan juga seleksi administratif yang tidak mudah. Pada kajian lainnya dijelaskan bahwa untuk menekan adanya ketidakdisiplinan pegawai yang mengakibatnya keluarnya personel dari instansi perlu dilakukan proses rekrutmen secara maksimal (Nguyen & Shao, 2019), sehingga didapatkan pegawai dengan kompetensi dan loyalitas tinggi (Firdaus, 2017).…”
Section: "Kalau Pandangan Saya Ndan Salah Satunya Dari Penyebab Untuk...unclassified
“…These findings are also supported by previous studies that revealed that job satisfaction significantly and negatively influenced employees' turnover intention. It means that employees' high job satisfaction will decrease their intention to quit their job [27][28][29][30][31].…”
Section: Multiple Regression Analysismentioning
confidence: 99%